Особенности биологических, психосоциальных и производственных факторов в психогенезе патологических реакций и состояний среди работников промышленных предприятий - Подлубный, В. Л.; Підлубний, Віталій Леонідович; Podlubnyi, V. L. (Одесский медицинский журнал, 2016)
Описаны и проанализированы результаты комплексной оценки дезадаптации работников промышленности. Обобщены биопсихосоциальные акценты в зависимости от стажа работы, вида труда, возраста, гендерных особенностей. Представлены акценты риска возникновения, а также развития дезадаптации при наличии соматических болезней. На основании обработки данных предложен модус психопрофилактики и психотерапевтического сопровождения с целью минимизации факторов, нарушающих адаптацию среди организованной промышленной популяции. The aim of this study was to establish the role of biological, psychosocial and occupational factors in the psychogenesis of pathological reactions and conditions among the organized industrial population. The studies were conducted on the basis of the Zaporozhian Regional Clinical Psychiatric Hospital during the 2008–2012 years. 982 workers were among the examined persons in conditions of informed consent. Examination included psychoprophylactic check-in. Clinico-epidemiological, clinical, psychopathological and statistical methods, especially exact Fisher’s test were used to achieve the aim of the study. The relative risk of mental adaptation disorders development was taken into consideration when evaluating factors psychogenesis of mental maladjustment among workers. The following group of potentially psychogenic factors were identified: the productive, biological and social factors. Among the identified risk factors responsible for significant dysadaptative reactions the most important was the influence of harmful factors such as “intensive vibration” (2.84 times higher), “increased noise level” (2.09 times higher), total labour time up to 10 years (1.93 times higher) and “increased dustiness” (1.86 times higher). The most significant factors causing persistent dysadaptative states were both productive factors such as “moderate labour” (2.9 times higher), “increased noise level” (2.29 times higher) and biological factors — “being a woman” (in 2.43 times higher), “age of the persons 50–60” (2.2 times higher). One could conclude that both psychoprophylactic and psychotherapeutic basis aimed to dysadaptative reactions minimization in industry workers should be based about the symptoms of these disorders as well as the relative risk of their occurrence under the influence of modifiable and nonmodifiable risk factors.
Characteristics of the biological, psychosocial and production factors in psychogenesis of pathological reactions and conditions among industrial workers
Keywords: промышленная популяция; психогенез; психическая дезадаптация; факторы риска; психотерапия; психопрофилактика; industrial population; psychogenesis; psychological maladjustment; risk factors; therapy; psychoprophylaxis